2011
DOI: 10.1016/j.yexmp.2011.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Foreign body-type multinucleated giant cells induced by interleukin-4 express select lymphocyte co-stimulatory molecules and are phenotypically distinct from osteoclasts and dendritic cells

Abstract: Foreign body-type multinucleated giant cells (FBGC), formed by macrophage fusion, are a prominent cell type on implanted biomaterials, although the roles they play at these and other sites of chronic inflammation are not understood. Why lymphocytes are present in this scenario and the effects of fusing macrophages/FBGC on subsequent lymphocyte responses are also unclear. To address the physiological significance of FBGC in this regard, we employed our in vitro system of interleukin (IL)-4-induced human monocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
27
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 41 publications
8
27
0
Order By: Relevance
“…For example, fusion of macrophages results in the formation of multinucleated giant cells (MNGs), which is a typical feature of granulomatous inflammation and foreign body reactions. [94][95][96][97][98] Moreno et al found that IL-4 induces MNG generation in a STAT6-dependent manner by regulating the expression of at least 2 fusion mediators, E-cadherin and DC-STAMP, resulting in homotypic macrophage fusion and engulfment of large foreign bodies. 99 In addition TREM-2 and its signaling association partner DAP12 are required for IL-4-induced E-cadherin and DC-STAMP expression, and giant cell formation in vitro and in vivo.…”
Section: E-cadherin Contributes To Macrophage Fusion and Osteoclastogmentioning
confidence: 99%
“…For example, fusion of macrophages results in the formation of multinucleated giant cells (MNGs), which is a typical feature of granulomatous inflammation and foreign body reactions. [94][95][96][97][98] Moreno et al found that IL-4 induces MNG generation in a STAT6-dependent manner by regulating the expression of at least 2 fusion mediators, E-cadherin and DC-STAMP, resulting in homotypic macrophage fusion and engulfment of large foreign bodies. 99 In addition TREM-2 and its signaling association partner DAP12 are required for IL-4-induced E-cadherin and DC-STAMP expression, and giant cell formation in vitro and in vivo.…”
Section: E-cadherin Contributes To Macrophage Fusion and Osteoclastogmentioning
confidence: 99%
“…Nevertheless, some reports have shown painful symptomatology associated with secondary infection [7][8] , and extension between 1 and 3 centimeters. However, cases of large dimensions have been reported 5,7 , as in the case here reported, the size of which at the largest diameters was 10.3 centimeters, covering the region from the premolars up to the body of the mandible.…”
Section: Discussionmentioning
confidence: 99%
“…Radiographically, OOCs present as well-delimited, and predominantly unilocular radiolucent lesions 2,5,8 that may be associated with the crown of an impacted tooth. It is frequently confused with the dentigerous cyst or with KOT 2,8 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations